Basalt fiber smc and method for manufacturing the same
Patent Information
- Application Number
- CN202311772526.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-21
- Publication Date
- 2026-10-09
AI Technical Summary
[0003]目前,片状模塑料的纤维以玻璃纤维和碳纤维为主,其中,玻璃纤维强度相对较弱,在生产中会产生玻璃纤维粉等废物,对环境及人体健康产生严重影响,且废弃物难以进行处理;而碳纤维成本较高,且由于其具有一定的电导性,难以满足有绝缘要求的相关应用
[0049]本发明提供了一种新型玄武岩纤维增强的片状模塑料(SMC)制备方法和理念。本发明以改性聚酯树脂为基体,以玄武岩纤维为增强体,辅以增稠剂、引发剂、阻聚剂、低收缩剂等助剂和改性无机填料,制备新型玄武岩纤维基模压片材及制品。借助玄武岩纤维的高强度、高模量及其与树脂基体的物理化学相容性,将进一步改善片材质量,并提升制品强度和稳定性。同时,玄武岩纤维SMC及其相关产品可在性能、功能、应用等方面实现对玻璃钢制品的替代和提升,且借助玄武岩纤维的自分解降解且无污染特性,极大降低退役产品的处置成本,并减少环境污染。玄武岩纤维SMC模压制品的拉伸强度可达到350MPa,压缩强度可超过450MPa,同时其表面电阻和体积电阻均高于传统的玻璃钢相关制品,尤其重要的是,玄武岩纤维SMC制备理念和制备方法的提出,将极大拓展玄武岩纤维的应用领域,促进行业和产业发展。
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite material technology, and in particular to a basalt SMC and its preparation method. Background Technology
[0002] Sheet molding compounds (SMCs) are sheet materials made primarily from thermosetting resins, with the addition of thickeners, low-shrinkage agents, release agents, fillers, and other additives, and reinforced with short-cut fibers (usually glass fibers or carbon fibers). Their molding process offers advantages such as high production efficiency, stable product quality, and low cost. They are suitable for the large-scale production of high-precision, structurally complex, and aesthetically demanding parts or products that can meet diverse requirements, and are widely used in the automotive, electronics, and infrastructure industries.
[0003] Currently, sheet molding compounds are mainly made of glass fiber and carbon fiber. Glass fiber has relatively weak strength and generates waste such as glass fiber powder during production, which has a serious impact on the environment and human health, and the waste is difficult to dispose of. Carbon fiber, on the other hand, is expensive and, due to its certain electrical conductivity, is difficult to meet the requirements of related applications with insulation requirements.
[0004] Basalt fiber, a widely available and environmentally friendly high-performance fiber, boasts advantages such as high strength, high modulus, high insulation, and high-temperature resistance. Furthermore, its production process does not generate harmful substances like boron or other alkali metal oxides, making it environmentally friendly. After natural degradation, basalt fiber becomes part of the soil matrix, causing no secondary pollution. Basalt fiber composites, using basalt fiber as the reinforcing material, outperform glass fiber reinforced composites in terms of high-temperature resistance, chemical stability, corrosion resistance, insulation, and abrasion resistance. They can also replace carbon fiber in certain technological fields, avoiding the drawbacks of severe carbon fiber shortages and high costs. In addition, basalt fiber exhibits excellent physicochemical compatibility with resin matrices, demonstrating higher interfacial bonding strength compared to glass fiber and carbon fiber.
[0005] Based on this, this invention proposes a design concept and preparation method for basalt fiber-reinforced sheet molding compound (SMC), providing effective assistance in improving the performance and recyclability of SMC products. This invention uses thermosetting resins such as polyester, polyurethane, and epoxy resin as the matrix, basalt fiber as the reinforcement, and supplements with low-shrinkage agents, curing agents, thickeners, release agents, and other additives to prepare a novel high-performance SMC. This SMC can then be used as a raw material for the design and preparation of novel high-performance molded products. Simultaneously, the novel SMC prepared by this invention will provide a new technical approach and material basis for the design, processing, and production of high-precision parts with high strength, high insulation, and high wear resistance. Summary of the Invention
[0006] This invention relates to the field of sheet molding compounds and compression molding composites, and provides a basalt SMC and its preparation method, the specific technical solution of which is as follows:
[0007] A type of basalt SMC, by weight, comprises the following components:
[0008] Modified polyester resin, 70-100 parts;
[0009] Low shrinkage agent, 20-40 parts;
[0010] Initiator, 0.5-1.5 parts;
[0011] Polymerization inhibitor, 1-2 parts;
[0012] Internal release agent, 1.5-4.5 parts;
[0013] Modified filler, 120-180 parts;
[0014] Thickener, 0.5-4.5 parts;
[0015] Reinforcement, 50-80 parts;
[0016] The method for preparing the modified polyester resin includes:
[0017] (1) During the esterification reaction of terephthalic acid and ethylene glycol, the graphene material dispersion is added to the reaction system at a rate of 5.0-7.0 mL / min;
[0018] (2) Polycondense the reaction product of esterification in step (1) to obtain a modified polyester resin.
[0019] The amount of graphene material added is 0.5-4% of the total mass of terephthalic acid and ethylene glycol added in step (1);
[0020] In step (1), nanocellulose is also dispersed in the graphene material dispersion;
[0021] The aspect ratio of the nanocellulose is 20:1 to 100:1.
[0022] In some embodiments, the method for preparing the modified filler includes:
[0023] (1) The filler was soaked in an acidic solution, filtered, and washed with water to obtain activated filler. Then, twice the amount of wetting agent was added to the activated filler and ultrasonically dispersed to obtain mixture I.
[0024] (2) Disperse the emulsifier in water, heat it to dissolve it, add the adhesive, and prepare an emulsion by mechanical stirring. Add the emulsion to the mixture I in step (1), continue to disperse it by ultrasonication, then filter and dry it to obtain the modified filler.
[0025] In some embodiments, the filler is one or two of aluminum hydroxide, diatomaceous earth, calcium carbonate, calcium sulfate, and talc.
[0026] Preferably, the filler is a mixture of aluminum hydroxide, diatomaceous earth, calcium carbonate, and calcium sulfate in a mass ratio of 1:1:1:1.
[0027] Preferably, the wetting agent is KH560.
[0028] Preferably, the emulsifier is Tween 20.
[0029] Preferably, the adhesive is epoxy resin.
[0030] In some embodiments, the low-shrinkage agent is styrene or a mixture of styrene and methyl methacrylate.
[0031] Preferably, the low-shrinkage agent is styrene.
[0032] In some embodiments, the initiator is one of organic peroxides such as benzoyl peroxide, tert-butyl peroxide, cyclohexanone peroxide, methyl ethyl ketone peroxide, and tert-butyl peroxide (2-ethylhexanoate).
[0033] Preferably, the initiator is benzoyl peroxide.
[0034] In some embodiments, the polymerization inhibitor is any one of p-benzoquinone, hydroquinone, p-tert-butylcatechol, and 2,6-di-tert-butyl-p-cresol.
[0035] Preferably, the polymerization inhibitor is p-benzoquinone.
[0036] In some embodiments, the internal release agent is one of lecithin, alkyl phosphatidic acid, stearic acid, and stearate.
[0037] Preferably, the internal release agent is lecithin.
[0038] In some embodiments, the thickener is one or more of magnesium oxide, magnesium hydroxide, calcium oxide, calcium hydroxide, and barium oxide.
[0039] Preferably, the thickener is a mixture of magnesium oxide, magnesium hydroxide, and calcium oxide in a mass ratio of 2:4:1.
[0040] In some embodiments, the reinforcement is short-cut basalt fiber with a diameter of 6-13 μm and a length of 35-55 mm.
[0041] A second aspect of this invention provides a method for preparing basalt SMC, comprising the following steps:
[0042] Step 1: Add modified polyester resin, low shrinkage agent, internal release agent, modified filler, and polymerization inhibitor to a mixing vessel equipped with a heating and heat preservation device in proportion. Then add initiator and thickener in proportion. After mixing and stirring evenly, a resin paste is obtained.
[0043] Step 2: Use a scraper to evenly coat the resin paste onto two layers of PE film, and then evenly disperse the basalt fiber onto the coated resin paste according to the specified proportions.
[0044] Step 3: Lay the two PE films containing resin paste and basalt fiber together to form a basalt fiber-based resin paste sheet with PE film on both the top and bottom.
[0045] Step 4: After the obtained resin paste sheet is rolled by a rolling roller, the basalt fiber is fully impregnated to obtain basalt fiber-based SMC sheet, and the sheet is then wound up.
[0046] Step 5: Place the wound sheet in a 45℃ drying room for thickening for 48-72 hours. Then remove it to obtain basalt fiber-based sheet molding compound.
[0047] Step Six: After peeling off the film from the cured sheet, cut the sheet to 290mm×290mm and calculate the number of layers to be laid according to the sample thickness at 0.5mm / layer SMC. Set the temperature of the 200-ton molding press to 150±2℃. After the temperature stabilizes, place the sheet in it. The mold size is 300×300mm. After closing the mold, the initial pressure is 0.5MPa, preheat for 45s, then increase the pressure to 5MPa, hold for 30s, and finally increase the pressure to 15MPa and hold. Determine the molding time according to 1min / mm. After pressing, remove the mold and take out the sample. After the sample cools to room temperature, trim the edges, inspect, process and test.
[0048] The beneficial effects of this invention are:
[0049] This invention provides a novel method and concept for preparing basalt fiber reinforced sheet molding compound (SMC). Using modified polyester resin as the matrix and basalt fiber as the reinforcement, and supplemented with thickeners, initiators, polymerization inhibitors, low-shrinkage agents, and modified inorganic fillers, this invention prepares novel basalt fiber-based molded sheets and products. Leveraging the high strength, high modulus, and physicochemical compatibility of basalt fiber with the resin matrix, the quality of the sheet material will be further improved, and the strength and stability of the products will be enhanced. Simultaneously, basalt fiber SMC and related products can replace and improve fiberglass products in terms of performance, function, and application. Furthermore, the self-degradable and pollution-free properties of basalt fiber significantly reduce the disposal costs of decommissioned products and minimize environmental pollution. Basalt fiber SMC molded products can achieve a tensile strength of 350MPa and a compressive strength of over 450MPa. At the same time, their surface resistivity and volume resistivity are higher than those of traditional fiberglass products. Most importantly, the proposed concept and method for preparing basalt fiber SMC will greatly expand the application fields of basalt fiber and promote the development of the industry. Detailed Implementation
[0050] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0051] In the following examples and comparative examples, the wetting agent is polyethylene glycol-400, and the adhesive is epoxy resin.
[0052] Example 1
[0053] A type of basalt SMC, by weight, comprises the following components:
[0054] Modified polyester resin, 80 parts;
[0055] Low-shrinkage styrene, 30 parts;
[0056] Initiator benzoyl peroxide, 1 part;
[0057] Polymerization inhibitor p-benzoquinone, 2 parts;
[0058] Lecithin, an inner mold release agent, 3 parts;
[0059] Modified filler, 150 parts;
[0060] Thickener, 3 parts;
[0061] Enhancer, 70 units;
[0062] The thickener is a mixture of magnesium oxide, magnesium hydroxide, and calcium oxide in a mass ratio of 2:4:1.
[0063] The reinforcement is short-cut basalt fiber with a diameter of 6-13 μm and a length of 35-55 mm.
[0064] The method for preparing the modified polyester resin includes:
[0065] A solution of graphene material, nanocellulose and ethylene glycol in a mass ratio of 1:5:8 was mixed and sonicated for 4 hours to obtain an ethylene glycol solution in which graphene material was dispersed.
[0066] (1) Terephthalic acid and ethylene glycol in a mass ratio of 1:2 were added to an esterification vessel, and triphenyl phosphite was added at the same time. The reaction was carried out at 245°C for 3 hours under an inert gas atmosphere. During the reaction, an ethylene glycol solution containing graphene material was added to the reaction system at a rate of 6.0 mL / min. The amount of graphene material added was 4% of the total mass of terephthalic acid and ethylene glycol, and the amount of triphenyl phosphite added was 0.01% of the total mass of terephthalic acid and ethylene glycol.
[0067] (2) The reaction product of esterification in step (1) was polycondensed at 240°C and 0.25 MPa for 2.8 h to obtain the modified polyester resin.
[0068] The method for preparing the modified filler includes:
[0069] (1) The filler (800-1000 mesh) was soaked in hydrochloric acid aqueous solution (2 mol / L), filtered, and washed with water to obtain activated filler. Then, twice the amount of wetting agent was added to the activated filler and ultrasonically dispersed to obtain mixture I.
[0070] (2) Disperse the emulsifier in water, heat it to dissolve it, add the adhesive, and prepare an emulsion by mechanical stirring. Add the emulsion to the mixture I in step (1), continue to disperse it by ultrasonication, then filter and dry it to obtain the modified filler.
[0071] The filler is a mixture of aluminum hydroxide, diatomaceous earth, calcium carbonate, and calcium sulfate in a mass ratio of 1:1:1:1.
[0072] A method for preparing basalt SMC includes the following steps:
[0073] Step 1: Add modified polyester resin, low shrinkage agent, internal release agent, modified filler, and polymerization inhibitor to a mixing vessel equipped with a heating and heat preservation device in proportion. Then add initiator and thickener in proportion. After mixing and stirring evenly, a resin paste is obtained.
[0074] Step 2: Use a scraper to evenly coat the resin paste onto two layers of PE film, and then evenly disperse the basalt fiber onto the coated resin paste according to the specified proportions.
[0075] Step 3: Lay the two PE films containing resin paste and basalt fiber together to form a basalt fiber-based resin paste sheet with PE film on both the top and bottom.
[0076] Step 4: After the obtained resin paste sheet is rolled by a rolling roller, the basalt fiber is fully impregnated to obtain basalt fiber-based SMC sheet, and the sheet is then wound up.
[0077] Step 5: Place the wound sheet in a 45℃ drying room for thickening for 48-72 hours. Then remove it to obtain basalt fiber-based sheet molding compound.
[0078] Step Six: After peeling off the film from the cured sheet, cut the sheet to 290mm×290mm and calculate the number of layers to be laid according to the sample thickness at 0.5mm / layer SMC. Set the temperature of the 200-ton molding press to 150±2℃. After the temperature stabilizes, place the sheet in it. The mold size is 300×300mm. After closing the mold, the initial pressure is 0.5MPa, preheat for 45s, then increase the pressure to 5MPa, hold for 30s, and finally increase the pressure to 15MPa and hold. Determine the molding time according to 1min / mm. After pressing, remove the mold and take out the sample. After the sample cools to room temperature, trim the edges, inspect, process and test.
[0079] Comparative Example 1
[0080] A type of basalt SMC, the specific implementation method is the same as in Example 1, except that:
[0081] By weight, it includes the following components:
[0082] Modified polyester resin, 180 parts;
[0083] Low-shrinkage styrene, 40 parts;
[0084] Initiator benzoyl peroxide, 1 part;
[0085] Polymerization inhibitor p-benzoquinone, 2 parts;
[0086] Lecithin, an inner mold release agent, 3 parts;
[0087] Modified filler, 300 parts;
[0088] Thickener, 3 parts;
[0089] Enhancer, 130 copies.
[0090] Comparative Example 2
[0091] A type of basalt SMC, the specific implementation method is the same as in Example 1, except that:
[0092] The thickener is a mixture of magnesium oxide and calcium oxide in a mass ratio of 2:1.
[0093] The reinforcement is short-cut basalt fiber with a diameter of 15-40 μm and a length of 50-70 mm.
[0094] Comparative Example 3
[0095] A type of basalt SMC, the specific implementation method is the same as in Example 1, except that:
[0096] The method for preparing the modified polyester resin includes:
[0097] Graphene material and ethylene glycol were mixed at a mass ratio of 1:8 and sonicated for 4 hours to obtain an ethylene glycol solution in which graphene material was dispersed.
[0098] (1) Terephthalic acid and ethylene glycol in a mass ratio of 1.3:1.5 were added to an esterification vessel, and triphenyl phosphite was added at the same time. The reaction was carried out at 245°C for 3 hours under an inert gas atmosphere. During the reaction, an ethylene glycol solution containing graphene material was added to the reaction system at a rate of 6.0 mL / min. The amount of graphene material added was 2% of the total mass of terephthalic acid and ethylene glycol, and the amount of triphenyl phosphite added was 0.01% of the total mass of terephthalic acid and ethylene glycol.
[0099] (2) The reaction product of esterification in step (1) was polycondensed at 240°C and 0.25 MPa for 2.8 h to obtain the modified polyester resin.
[0101] Comparative Example 4
[0102] A type of basalt SMC, the specific implementation method is the same as in Example 1, except that:
[0103] The method for preparing the modified filler includes:
[0104] (1) The filler (1300 mesh) was soaked in hydrochloric acid aqueous solution (2 mol / L), filtered, and washed with water to obtain activated filler. Then, twice the amount of wetting agent was added to the activated filler and ultrasonically dispersed to obtain mixture I.
[0105] (2) Disperse the emulsifier in water, heat it to dissolve it, add the adhesive, and prepare an emulsion by mechanical stirring. Add the emulsion to the mixture I in step (1), continue to disperse it by ultrasonication, then filter and dry it to obtain the modified filler.
[0106] The filler is a mixture of aluminum hydroxide and diatomaceous earth in a mass ratio of 1:1.
[0107] A method for preparing basalt SMC, the specific implementation method is the same as in Example 1.
[0108] Comparative Example 5
[0109] A basalt SMC, the specific implementation method is the same as in Example 1, except that the filler is not modified.
[0110] Comparative Example 6
[0111] A type of basalt SMC, the specific implementation method is the same as in Example 1, except that:
[0112] The filler is a mixture of aluminum hydroxide, diatomaceous earth, calcium carbonate, and calcium sulfate in a mass ratio of 3:4:1:2.
[0113] Performance testing
[0114] The mechanical strength of the basalt SMC prepared in the examples and comparative examples was tested, and the results are shown in Table 1:
[0115] Table 1
[0116] Tensile strength (MPa) Compressive strength (MPa) Example 1 350 450 Comparative Example 1 312 415 Comparative Example 2 335 413 Comparative Example 3 323 431 Comparative Example 4 362 422 Comparative Example 5 332 429 Comparative Example 6 276 388
[0117] As shown in Table 1, the basalt SMC prepared by this invention, using modified polyester resin as the matrix, basalt fiber as the reinforcement, and supplemented with thickeners, initiators, polymerization inhibitors, low-shrinkage agents, and modified inorganic fillers, exhibits excellent mechanical properties, especially tensile and compressive strength, which are better than those of basalt SMC prepared by similar methods in the prior art. Extensive comparative experiments show that when the component ratio, types of substances, modification methods, and reagents used are changed, the tensile and compressive strengths of the comparative samples all show a significant decrease, indicating the uniqueness of the technical solution in Example 1 of this invention. Therefore, only the basalt SMC prepared using the complete technical solution of the examples exhibits the best performance.
[0118] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A type of basalt SMC, characterized in that, By weight, it includes the following components: Modified polyester resin, 70-100 parts; Low shrinkage agent, 20-40 parts; Initiator, 0.5-1.5 parts; Polymerization inhibitor, 1-2 parts; Internal release agent, 1.5-4.5 parts; Modified filler, 120-180 parts; Thickener, 0.5-4.5 parts; Reinforcement, 50-80 parts; The method for preparing the modified polyester resin includes: (1) During the esterification reaction of terephthalic acid and ethylene glycol, the graphene material dispersion is added to the reaction system at a rate of 5.0-7.0 mL / min; (2) Polycondense the reaction product of esterification in step (1) to obtain a modified polyester resin. The amount of graphene material added is 0.5-4% of the total mass of terephthalic acid and ethylene glycol added in step (1); In step (1), nanocellulose is also dispersed in the graphene material dispersion; The aspect ratio of the nanocellulose is 20:1 to 100:
1.
2. The basalt SMC according to claim 1, characterized in that, The method for preparing the modified filler includes: (1) The filler was soaked in an acidic solution, filtered, and washed with water to obtain activated filler. Then, twice the amount of wetting agent was added to the activated filler and ultrasonically dispersed to obtain mixture I. (2) Disperse the emulsifier in water, heat it to dissolve it, add the adhesive, and prepare an emulsion by mechanical stirring. Add the emulsion to the mixture I in step (1), continue to disperse it by ultrasonication, then filter and dry it to obtain the modified filler.
3. The basalt SMC according to claim 2, characterized in that, The filler is one or two of aluminum hydroxide, diatomaceous earth, calcium carbonate, calcium sulfate, and talc.
4. The basalt SMC according to claim 1, characterized in that, The low-shrinkage agent is styrene or a mixture of styrene and methyl methacrylate.
5. The basalt SMC according to claim 1, characterized in that, The initiator is one of the organic peroxides such as benzoyl peroxide, tert-butyl peroxide, cyclohexanone peroxide, methyl ethyl ketone peroxide, and tert-butyl peroxide (2-ethylhexanoate).
6. The basalt SMC according to claim 1, characterized in that, The polymerization inhibitor is any one of p-benzoquinone, hydroquinone, p-tert-butylcatechol, and 2,6-di-tert-butyl-p-cresol.
7. The basalt SMC according to claim 1, characterized in that, The internal release agent is one of lecithin, alkyl phosphatidic acid, stearic acid, and stearate.
8. The basalt SMC according to claim 1, characterized in that, The thickener is one or more of magnesium oxide, magnesium hydroxide, calcium oxide, calcium hydroxide, and barium oxide.
9. The basalt SMC according to claim 1, characterized in that, The reinforcement is short-cut basalt fiber with a diameter of 6-13 μm and a length of 35-55 mm.
10. A method for preparing basalt SMC, characterized in that, Includes the following steps: Step 1: Add the modified polyester resin, low shrinkage agent, internal release agent, modified filler, and polymerization inhibitor to a mixing vessel equipped with a heating and heat preservation device in proportion. Then, add the initiator and thickener in proportion. After mixing and stirring evenly, a resin paste is obtained. Step 2: Use a scraper to evenly coat the resin paste onto two layers of PE film, and then evenly disperse the basalt fiber onto the coated resin paste according to the specified proportions. Step 3: Lay the two PE films containing resin paste and basalt fiber together to form a basalt fiber-based resin paste sheet with PE film on both the top and bottom. Step 4: After the obtained resin paste sheet is rolled by a rolling roller, the basalt fiber is fully impregnated to obtain basalt fiber-based SMC sheet, and the sheet is then wound up. Step 5: Place the wound sheet in a 45℃ drying room for thickening for 48-72 hours. Then remove it to obtain basalt fiber-based sheet molding compound. Step Six: After peeling off the film from the cured sheet, cut the sheet to 290mm×290mm and calculate the number of layers to be laid according to the sample thickness at 0.5mm / layer SMC. Set the temperature of the 200-ton molding press to 150±2℃. After the temperature stabilizes, place the sheet in it. The mold size is 300×300mm. After closing the mold, the initial pressure is 0.5MPa, preheat for 45s, then increase the pressure to 5MPa, hold for 30s, and finally increase the pressure to 15MPa and hold. Determine the molding time according to 1min / mm. After pressing, remove the mold and take out the sample. After the sample cools to room temperature, trim the edges, inspect, process and test.